Assessment of risk factors on morbidity and mortality in patients undergoing percutaneous endoscopic gastrostomy (Annals of Medical Research, 2021)
None
Keywords: Complication; Mortality; Percutaneous Endoscopic Gastrostomy (PEG); Peristomal Leakage.